2016
DOI: 10.1103/physrevd.94.034001
|View full text |Cite
|
Sign up to set email alerts
|

LHC constraints and prospects forS1scalar leptoquark explaining theB¯D(*

Abstract: Recently, deviations in flavor observables ofB → D ( * ) τν have been shown between the predictions in the Standard Model and the experimental results reported by BaBar, Belle, and LHCb collaborations. One of the solutions to this anomaly is obtained in a class of leptoquark model with a scalar leptoquark boson S 1 , which is a SU (3) c triplet and SU (2) L singlet particle with −1/3 hypercharge interacting with a quarklepton pair. With well-adjusted couplings, this model can explain the anomaly and be compati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
57
0
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(58 citation statements)
references
References 101 publications
0
57
0
1
Order By: Relevance
“…It is found that the values of the ratios R D ( * ) ≡ B(B → D ( * ) τ −ν τ )/B(B → D ( * ) −ν ) ( = e, µ) considerably exceed their SM predictions. Assuming Gaussian distributions, and taking correlations into account, the experimental results and theoretical predictions can be combined to yield [22,23] The measured values of R D and R D * represent deviations from the SM of 1.7σ and 3.1σ, respectively. These are known as the R D and R D * puzzles.…”
Section: R D ( * )mentioning
confidence: 99%
“…It is found that the values of the ratios R D ( * ) ≡ B(B → D ( * ) τ −ν τ )/B(B → D ( * ) −ν ) ( = e, µ) considerably exceed their SM predictions. Assuming Gaussian distributions, and taking correlations into account, the experimental results and theoretical predictions can be combined to yield [22,23] The measured values of R D and R D * represent deviations from the SM of 1.7σ and 3.1σ, respectively. These are known as the R D and R D * puzzles.…”
Section: R D ( * )mentioning
confidence: 99%
“…In ref. [65], several leptoquark models are considered that generate scalar, vector, and tensor operators. The SU(3)×SU(2)×U(1) quantum numbers of these models are summarized in table 5.…”
Section: Jhep08(2017)131mentioning
confidence: 99%
“…Previous analyses in the literature have considered various ad hoc extensions of the Standard Model suitable to accommodate the anomalies, in particular including new gauge bosons [25][26][27][28][29][30][31][32][33][34][35], leptoquarks [36][37][38][39][40][41][42][43][44][45][46][47][48][49][50] and general effective field theory frameworks [51][52][53][54][55]. 2 Anomalies in R K , and b → s processes, have also been addressed in Randall-Sundrum [56][57][58] and flat space [59] extra dimensional scenarios.…”
Section: Jhep07(2017)102mentioning
confidence: 99%